Разработка экспериментального оборудования для создания эффективных контактных устройств ректификационных колон - Соколов, Михаил Владимирович; Ульев, Леонид Михайлович; Сулима, А. Н. (НТУ "ХПИ", 2012)
The problems of effective contact facility of distillation column are discussed in the paper. The base directions of improving for contact devices column apparatuses were defined. The construction of experimental facilities to study and developing new methods of calculation of internal devices for rectification, absorption and distillation were processed.
Keywords: тепломассообмен; контактные устройства; турбулизация; насадочные аппараты; тарельчатые аппараты; колонные аппараты